DIVERTERLESS SUPERSONIC INLET DESIGN AND ANALYSIS FOR FIGHTER-X UNDERGRADUATE FINAL PROJECT - Hasan Izzuddin, Muhammad
This final project deals with the design and analysis of a diverterless supersonic inlet (DSI) for a 4.5 generation fighter jet (Fighter-X). The main motivation in choosing this topic is because DSI is the most intriguing topic to the author and a topic explored by some military aircraft industries developing modern fighter aircraft. The focus of the final project is to design and analyze the bump geometry of a DSI in a supersonic cruise flight condition. The method is to design and analyze some bump geometries on a flat surface, study the behaviour and effect of the selected bump geometry when combined with a forward swept cowl geometry to make DSI, and implement the DSI design to Fighter-X. The goal is to obtain a quantitative prediction on the flow compression and inlet performance for various bump geometries and to implement the optimum design for Fighter-X. Predictions are made by Computational Fluid Dynamics (CFD) simulation by solving Favre Averaged Navier-Stokes equation with shear stress transport turbulence modelling using ASNYS CFX software and compared with some literature references. Bump geometry are designed and analysed starting from the simplest to the complex ones and meshed using unstructured tetrahedral meshing scheme for numerical analysis in ANSYS CFX. Analysis is carried out at different Mach Numbers to analyze different flow features such as pressure recovery and boundary layer diversion. Finally, the DSI is integrated based on available Fighter-X inlet data. The result from this final project is a baseline in designing DSI as well as a DSI design installed on Fighter-X.